2010
DOI: 10.3121/cmr.2010.902
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome: Comparison of Occurrence Using Three Definitions in Hypertensive Patients

Abstract: Objective:To compare the frequency of occurrence of metabolic syndrome using three international definitions and to study the distribution of cardiovascular risk factors among newly diagnosed hypertensive Nigerian subjects.Design: Cross sectional study.Settings: Cardiology unit of LAUTECH Teaching Hospital, Osogbo, Nigeria. Participants:One hundred forty newly diagnosed hypertensive Nigerian subjects, and 70 normotensive controls (age-and sex-matched) were included in this study. Methods:Clinical history and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 29 publications
3
54
0
Order By: Relevance
“…The presence of MetS increases the risk for developing cardiovascular disease, diabetes, disability, and mortality (Lakka et al, 2002;Yamada et al, 2007;Cornier et al, 2008;Duvnjak and Duvnjak, 2009;Meshkani and Adeli, 2009;Gupta and Gupta, 2010;Akintunde et al, 2011). MetS development has been attributed to environmental factors (diet vs bad food habits; physical activity vs sedentary lifestyle), as well as to genetic polymorphisms known to be risk factors for cardiovascular disease, diabetes or inflammatory conditions (Lakka et al, 2002;Yamada et al, 2007;Ordovas and Shen, 2008;Meshkani and Adeli, 2009;Dalle et al, 2010;Monteiro and Azevedo, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of MetS increases the risk for developing cardiovascular disease, diabetes, disability, and mortality (Lakka et al, 2002;Yamada et al, 2007;Cornier et al, 2008;Duvnjak and Duvnjak, 2009;Meshkani and Adeli, 2009;Gupta and Gupta, 2010;Akintunde et al, 2011). MetS development has been attributed to environmental factors (diet vs bad food habits; physical activity vs sedentary lifestyle), as well as to genetic polymorphisms known to be risk factors for cardiovascular disease, diabetes or inflammatory conditions (Lakka et al, 2002;Yamada et al, 2007;Ordovas and Shen, 2008;Meshkani and Adeli, 2009;Dalle et al, 2010;Monteiro and Azevedo, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the prevalence was higher among women than men, 15-19-23-26 and with the IDF definition. [18][19][20][21][22][23][24][25][26] In order to make comparison among various studies possible, a new criterion which harmonizes the previous definitions was proposed. 34 However, there is scanty report on the prevalence of MS with the harmonized criteria Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…17,[18][19][20] Among patients with type 2 diabetes, prevalence of MS ranged between 59.1%-87.1%, [21][22][23][24] while in patients with hypertension, the prevalence ranged between 24.7%-40.74%. [17][18][19][20][21][22][23][24][25] These Nigerian authors used the WHO, IDF, and Adult Treatment Panel (ATP-III) criteria in their studies. Prevalence rates for MS in Ghana, 26 Cameroon, 27 South Africa, 28 India, 29 America, 30,31 United Kingdom 32 and Europe 33 ranged between 0% to 49.2% depending on the population studied and the criteria used.…”
Section: Introductionmentioning
confidence: 99%
“…However, some authors reported it as low as 29-35% [5,6]. This variation in prevalence of MS can be explained by different factors like ethnicity, age, gender distribution, duration of hypertension, sample size, type of study and criteria used.…”
Section: Discussionmentioning
confidence: 85%
“…So, it is important to know the proportion of hypertensive subjects having metabolic syndrome (MS). The prevalence of MS varies from 29% to 68% among hypertensive patients in different studies [3][4][5][6]. As a resource poor country, it may not be possible to screen all hypertensive subjects for the presence of MS.…”
Section: Introductionmentioning
confidence: 99%